INFLUENCE OF DESTINATION IMAGE, CONSUMER EXPERIENCE, AND PERCEIVED VALUE ON LOYALTY THROUGH SATISFACTION AS A MEDIATION VARIABLE - Widia Lestari Hasibuan; Heriyana; Ikramuddin; Halida Bahri (PT. Radja Intercontinental Publishing, 2026)
Abstract This study aims to analyze the effects of destination image, consumer experience, and perceived value on loyalty in Lake Toba, with satisfaction as a mediating variable. Using a quantitative approach, data were collected via a 5-point Likert scale questionnaire from 145 respondents selected through purposive sampling. Data analysis was performed using Partial Least Square Structural Equation Modeling (PLS-SEM) via SmartPLS 4.0. The results show that all hypotheses are accepted at a 5% significance level (P<0,000). Destination image, consumer experience, and perceived value have positive and significant effects on both satisfaction and loyalty (β=0.287 to β=0,410). Furthermore, satisfaction partially mediates the relationship between the three independent variables and loyalty (β=0,103 to β=0,145). These findings confirm the vital role of enhancing destination image, consumer experience, and perceived value in building long-term satisfaction and loyalty. Practically, this study provides insights for destination managers to design strategies that improve service quality and competitiveness in Lake Toba.